PELATIHAN PEMBUATAN DESAIN KEMASAN MENGGUNAKAN CANVA PADA UKM DESA KEDUNGGEDE UNTUK MENINGKATKAN DAYA SAING PRODUK - Don Avian Safitri; Retno Waluyo; Ito Setiawan (Yayasan Nusantara Hasana Berdikari, 2023)
It is felt that monotonous packaging designs do not function optimally from a visual perspective. Ideally, a product always has an attractive packaging that makes it a separate brand image to distinguish its identity from other products. The purpose of this service is to have training in making this packaging design which can foster a sense of creativity and create innovation, especially in making packaging designs. This packaging design training is aimed at UKMs in Kedunggede Village. The method used is literature review and demonstration via Zoom Meeting. The tool used in this packaging design service is Canva. In carrying out this activity, 14 people involved in the corn vermicelli cenil business participated. The results of this service activity are direct practice in making packaging designs and increasing knowledge and insight in implementing attractive packaging designs.